Respuesta :

The answer to your question is k (-3) = 21!

Here's how I got this answer:

K(a) = 2a^2 - a

K(a) = 2a^2 - a K(-3) = 2(-3)^2 - (-3)

K(a) = 2a^2 - a K(-3) = 2(-3)^2 - (-3)K(-3) = 2(9) + 3

K(a) = 2a^2 - a K(-3) = 2(-3)^2 - (-3)K(-3) = 2(9) + 3K (-3) = 18 + 3

K(a) = 2a^2 - a K(-3) = 2(-3)^2 - (-3)K(-3) = 2(9) + 3K (-3) = 18 + 3K (-3) = 21

I hope this helps!

Also sorry for the late answer, I just got the notification that you replied to my comment, I hope I came in time!

ACCESS MORE